2011
DOI: 10.1007/s00044-011-9667-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodimerization of heteroaryl chalcones: comparative antimicrobial activities of chalcones and their photoproducts

Abstract: The heterocyclic analogues of chalcones were synthesized by Claisen Schmidt reaction of (a) benzaldehyde with 2-acetylfurane, 2-acetylpyrrole and 2-acetylthiophene and (b) acetophenone with furfural, thiophene-2-carbaldehyde and pyrrole-2-carbaldehyde. The photolysis of class (a) and (b) chalcones under UV lamp gave different products. The stereoselective photodimerization of 1-(furane-2-yl)-3-phenylprop-2-en-1-one (1), 3-phenyl-1-(1H-pyrrole-2-yl)-prop-2-en-1-one (2) gave b-truxinic type dimers, (3,4-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The reaction was not sensitive to steric hindrance in the aldehyde, since it tolerates well the presence of ortho substituents (compare the yields in entries 4-5, 7-9 and 15-16). Generally speaking, the substituents at the aromatic ring of the aldehyde component did not have a significant influence in the yield, but it is remarkable that some of the best results corresponded to reactions with methoxybenzaldehyde derivatives (entries 2,11,15,20), in spite of the fact that the electron-releasing nature of the methoxy substituent should lead to a lower reactivity as electrophiles. Since the catalytic affect of the clay can be attributed to the Lewis acid activity of its metallic centers (Scheme 2a), the good reactivity of the methoxy derivatives can be explained by accepting that coordination of the oxygen atom in the OMe group with cationic centers in the clay attenuates its electron-releasing effect (Scheme 2b) [40].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The reaction was not sensitive to steric hindrance in the aldehyde, since it tolerates well the presence of ortho substituents (compare the yields in entries 4-5, 7-9 and 15-16). Generally speaking, the substituents at the aromatic ring of the aldehyde component did not have a significant influence in the yield, but it is remarkable that some of the best results corresponded to reactions with methoxybenzaldehyde derivatives (entries 2,11,15,20), in spite of the fact that the electron-releasing nature of the methoxy substituent should lead to a lower reactivity as electrophiles. Since the catalytic affect of the clay can be attributed to the Lewis acid activity of its metallic centers (Scheme 2a), the good reactivity of the methoxy derivatives can be explained by accepting that coordination of the oxygen atom in the OMe group with cationic centers in the clay attenuates its electron-releasing effect (Scheme 2b) [40].…”
Section: Resultsmentioning
confidence: 97%
“…These properties include antineoplastic [5][6][7], antimalarial [8], antiviral (HIV) [9,10], antibacterial [4,11,12], antioxidant [12] and anti-inflammatory [4,13] activities, among others. These compounds are also flexible scaffolds for the construction of five-and six-membered rings or their subsequent elaboration into polycyclic systems [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They exhibit several types of biological activity which varies according to the different substituents in the molecules. Thus, they show good potential for further studies and have attracted considerable interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, chalcones, 1,3-diaryl-2-propen-1-ones, consist of open-chain flavonoids in which the two aromatic rings are joined by a 3-carbon α,β-unsaturated carbonyl system. [2][3][4] Recently, Tavares et al 1 developed a series of new 6-quinolinyl N-oxide chalcones as well as the 6-quinolinyl chalcones and N-methyl quinolinium iodide derivatives and evaluated their antifungal and cytotoxic activities. The results showed that the majority of these chalcones demonstrated strong activity against pathogenic fungi and tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation